2019
DOI: 10.3390/nu11092232
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of B Vitamin Supplementation on Depressive Symptoms, Anxiety, and Stress: Effects on Healthy and ‘At-Risk’ Individuals

Abstract: A systematic review and meta-analysis was undertaken to examine and quantify the effects of B vitamin supplementation on mood in both healthy and ‘at-risk’ populations. A systematic search identified all available randomised controlled trials (RCTs) of daily supplementation with ≥3 B group vitamins with an intervention period of at least four weeks. Random effects models for a standardized mean difference were used to test for overall effect. Heterogeneity was tested using the I2 statistic. Eighteen articles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 55 publications
1
58
0
5
Order By: Relevance
“…Cognitive performance, and especially fluid intelligence, appeared improved following multiple micronutrient supplementation in an analysis of 18 randomised controlled trials in school-aged children [215], confirming an earlier meta-analysis in this age group [216]. In adults, the available data suggest an improvement of psychological and cognitive functions following multiple supplementations, based on several reviews [94,217] and on meta-analyses of intervention trials addressing mood and psychological state [218,219]. Regarding mood, the most recent meta-analysis found that in 11 out of 18 trials a combination of B vitamins resulted in improvement of mood when compared with a placebo.…”
Section: Effect Of Supplementation With Multiple Micronutrients On Mesupporting
confidence: 54%
See 1 more Smart Citation
“…Cognitive performance, and especially fluid intelligence, appeared improved following multiple micronutrient supplementation in an analysis of 18 randomised controlled trials in school-aged children [215], confirming an earlier meta-analysis in this age group [216]. In adults, the available data suggest an improvement of psychological and cognitive functions following multiple supplementations, based on several reviews [94,217] and on meta-analyses of intervention trials addressing mood and psychological state [218,219]. Regarding mood, the most recent meta-analysis found that in 11 out of 18 trials a combination of B vitamins resulted in improvement of mood when compared with a placebo.…”
Section: Effect Of Supplementation With Multiple Micronutrients On Mesupporting
confidence: 54%
“…Benefits on depressive symptoms failed to reach statistical significance, but conclusions were stronger for stress. Supplementation was more efficient in populations with a poor mood status or a poor nutrient status at baseline [219]. To illustrate this conclusion, one trial has shown that, compared with placebo, a 4 week supplementation (B vitamins, vitamin C, zinc, calcium and magnesium) in 58 healthy adults was associated with a significant improvement of mood, in relation to increased levels of B vitamins and lowered homocysteine in blood [220].…”
Section: Effect Of Supplementation With Multiple Micronutrients On Mementioning
confidence: 99%
“…The complex relationship between malnutrition, depression, and polypharmacy during aging has been explored and there is evidence of reverse causation [14,37,53,[57][58][59]. Longitudinal designs and structural equation models might be helpful for analyzing these interdependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of vitamins have also been studied by Kafeshani M et al In over 3,000 adults, they found that only women have high vitamin B6 levels that significantly reduce the likelihood of not only depression but also anxiety disorders [29]. A positive effect on the mood was confirmed by 11 of 18 articles on B vitamins and the placebo effect [30]. Vitamin D and paricalcitol are similarly important in the antidepressant and anxiety effect in a WAG / Rij rats study [31].…”
Section: The Influence Of Diet On An Anxietymentioning
confidence: 92%